A Study of Clustering Algorithm for Student Analysis - Janghel, Bhawna; Ambhaikar, Asha (International Journal of Computer Sciences and Engineering, 2019)
In this paper using k-mean clustering method use for students school academic performance are measured by quarterly exam, half yearly exam, and final exams result. So, by taking the marks of three of exams, we can compare the final result of govt. school data and private school data. By using data clustering technique we can predict which school is best.And try to identify the weak student of particular school and will identify the result of best school.This will lead to the identification of best between private & government school in town.Strategies and techniques of best school will be followed which will help in making the education system better.